Understanding the Educational and Social Difficulties in Children with Hemifacial Microsomia – A Literature Review - Pniak, Michał; Miklis, Paweł; Mawlichanów, Maciej; Ciesielska, Aleksandra; Sieradzka, Aleksandra; Szerej, Krzysztof; Czaplińska-Paszek, Zofia; Kot, Alicja; Wojtczak, Marta; Myśliwiec , Natalia; et al. (Quality in Sport, 2024)
Introduction: Hemifacial microsomia (HFM) is a congenital craniofacial defect, the second most common after cleft lip and palate. It is characterized by a wide range of symptoms, including mandibular hypoplasia, ear anomalies, and soft tissue defects. Patients may experience difficulties in learning, communication, and social relationships, which affect their quality of life and self-esteem. Study aims to evaluate the impact of defect on the neurodevelopmental and psychosocial outcomes in affected children. Materials and methods: Materials for the review were selected based on an analysis of publications published in the last 20 years. Results: In HFM patients with microtia, mandibular hypoplasia, young maternal age, and additional developmental anomalies, worse outcomes were observed in verbal, non-verbal, and academic skills. Studies on emotional functioning demonstrated a similar level of behavioral adjustment compared to control groups. Adolescents with HFM exhibited a lower tendency toward aggression and rule-breaking. Social problems, such as less frequent contact with peers or rejection by the group, were more common. This was particularly true for children with microtia and mandibular hypoplasia. Discussion: New studies emphasize that although some young children initially do not exhibit neurological or language deficits, there is an increased risk of educational and psychosocial difficulties in later life. Attention should be paid to patients with mandibular hypoplasia, microtia, and additional defects. Negative experiences in peer relationships and hearing loss may further adversely affect self-esteem and social functioning. Conclusions: HFM can affect the neurological and psychosocial development of children, especially in language and educational areas. Early intervention, assessment of psychosocial problems, provision of appropriate educational resources, and psychological support are crucial to improving patients’ quality of life.